Weighted Exponential Distribution: Approximate Bayes Estimations with Fuzzy Data - Al-Noor, Nadia Hashim; Hussein, Lamyaa K (Al-Nahrain Journal of Science, 2018)
This paper aims to focus on Bayes estimations for the shape and scale parameters along with the reliability function of weighted exponential distribution with fuzzy data. Bayes estimations have been obtained using symmetric and asymmetric loss functions. Lindley's approximation method has been used for the integrals that cannot be solved in closed form. At the end, some comparison for Bayes estimations are studied through a Monte Carlo simulation study.